Screening for Water Deficit Tolerance, Relative Growth Analysis and Agrobacterium-Infectivity in Tropical Maize [Zea Mays L.] Inbred Lines in Nairobi, Kenya - Olive, Sande F.; Njoka, Fredrick M.; Mgutu, Allan J.; Anami, Sylvester E. (My University, 2014)
The gap between maize demand and regional supply is increasing as small-holder farmers grapple with many challenges, key among them drought. Research in identifying maize lines that are tolerant to water deficit and that are amenable to A. tumefaciens-mediated transformation is a step towards enhancing food security. The objectives of this study were, to assess the physiological response of tropical maize inbred lines to water deficit, to determine whether A. tumefaciens elicits host resistance when in contact with zygotic embryos and determine if YEP is an effective infection medium compared to MS medium in immature zygotic embryo infection. Tropical maize lines CML 395, CML 216, CML 144, TL 21, A 04, E 04 and T 04 and Agrobacterium strain EHA101 habouring pTF102 vector containing GUS reporter gene were used. Physiological response of tropical maize genotypes to drought stress was evaluated by measuring plant height, leaf length, leaf width and fresh weight. T 04 and CML 216 seedlings exhibited the fastest growth rates of 4.33 cm and 4.28 cm respectively between the 7th and 8th day post leaf four emergence while TL 21 and CML 395 seedlings had the lowest rates of 2.93 cm and 3.59 cm respectively under normal growth conditions. A 04 seedlings exhibited the highest differences in fresh weight between stressed and unstressed plants [56.13 gm] while CML 216 seedlings had the lowest [24.57 gm]. Upon salt stress, leaf discs of CML 216 seedlings, exhibited low chlorophyll a: b ratios of 0.84, 0.78, 0.74, 0.75 and 0.70 in 100 mM, 125 mM, 150 mM, 175 mM and 200 mM NaCl concentrations respectively, while leaf discs of CML 144 seedlings exhibited higher chlorophyll a: b ratios of 1.51, 1.19, 1.24, 1.26, 1.45 and 1.39 under the same concentrations. The use of YEP medium in contrast to MS medium led to an improvement in transient GUS expression observed in immature embryos and significant increase in transformation frequency. The transformation protocol using YEP infection media as used in this study should be optimized and used in transformation of tropical maize inbreds.
Keywords: Transformation; A. tumefaciens; zygotic embryo; vector; water deficit; senescence; Genotype; phytohormones; transgene; recalcitrant